Intense World Theory: New Perspective in Brain\'s Function and the Role of Amygdala in Autism Spectrum Disorder - Shohreh Rahimian; Seyyed Amir Amin Yazdi; Imanollah Bigdeli; Mohammad Amin Edalatmanesh (Fasa University of Medical Sciences, 2019)
Background & Objective: In Autism Spectrum Disorder, the role of functional deficit like hypo-functionality in Frontal lobe, Hippocampus, Amygdala with top-down control hypothesis or reduced functional connectivity has been considered by theories like theory of mind or executive function theory. But new findings in the fields of neurobiology and neuroscience have challenged these theories and these lead to a new theory that was introduced by Hennry Markram in 2007. This theory is presented as "Intense World Theory". Markram believes that hyper-functionality, hyper-reactivity and Hyper-plasticity in brain's microcircuits with a down-up pathway is the basis of Autism. Conclusion: In this study various aspects of intense world theory, empirical evidence, and challenges and criticisms of this theory are discussed. In addition to creating a new research scope and paying attention to the underlying mechanisms of the brain, this review may lead to early diagnosis of disorder and effective therapeutic procedure in the medical, psychological and other fields.